Risk Mitigation in the Sacrificial Cattle Supply Chain in Indonesia: A Supply Chain Management (SCRM) Approach - Vikaliana, Resista; Awanis, Anggita (Jurnal Ilmiah Teknik Industri, 2024)
Paskas Farm is one of the cattle farms located in the Tangerang City area. This Paskas farm has a supply chain business process, namely small-sized cattle imported from the island of Java, namely Yogyakarta, Banyuwangi and Kediri. Then the cows are bred at the farm until they are large and have enough weight to be distributed for the benefit of Eid al-Adha. One of the supply chain risks at Paskas Farms related to animal welfare is during transportation and distribution. The transportation of this sacrificial cow takes a long time, namely for 16 hours, causing this sacrificial cow to experience stress during the distribution trip. The tight capacity in the truck also makes the sacrificial cattle experience stress because they do not implement animal welfare. Mitigation plans really need to be done to prevent or reduce the emergence of causes of risk. This study aims to determine the supply chain business process flow for qurban cattle from Paskas Farms, find out what risk events and the causes of priority risks that can arise in the supply chain business processes for sacrificial cattle at Paskas Farms, find out the appropriate handling strategy for priority risk causes in the process supply chain business for sacrificial cattle at Paskas Farm. Therefore, risk identification is carried out using the House of Risk phase 1 method which is grouped based on 5 main processes plan, source, make, deliver, return. From this process it was identified that there were 38 risk events and 24 risk agents. The recommended mitigation action or treatment strategy for the cause of the risk with the highest ranking is by using the House of Risk phase 2 method and get the result that there are 9 recommendations for mitigation actions that can be implemented by Paskas Farms.